Attitude and Behaviour Intention of Muslim Z Generation to Save in Islamic Banks: The Role of Knowledge and Religiosity - Purwanto, Purwanto; Dasuki, Ali Ibrahim; Ghofur, Abdul; Abdullah, Shodiq (Economica: Jurnal Ekonomi Islam, 2022)
This study aims to investigate the impact of knowledge and religiosity on attitudes toward Islamic banks and the saving intentions of Generation Z Muslims. Data were collected using a convenience sampling method from students at Islamic higher education institutions in Central Java, Indonesia. A total of 210 respondents aged 17-27 participated in the study. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that both knowledge and religiosity significantly shape attitudes toward Islamic banks among Generation Z Muslims. Knowledge emerged as the most influential factor shaping attitudes. Attitudes, in turn, significantly influence the saving intentions of Generation Z Muslims at Islamic banks. This study further demonstrates that attitudes are the strongest determinant of the saving intentions of Generation Z Muslims at Islamic banks. Practically, this research provides valuable insights for Islamic bank marketers in formulating strategies to attract Generation Z Muslims to save in Islamic banks. Theoretically, this study affirms the importance of integrating cognitive, affective, and spiritual dimensions in consumer behavior analysis to better understand and predict behavior.